Longevity/fecundity tradeoff in Caenorhabditis elegans by unfavorable bacteria Microbacterium sp. newly isolated from forest - Le, Tho Son; Nguyen, Thi Thu Hang; Nguyen, Thi Thu (Vietnam Journal of Biotechnology, 2025)
Bacteria are food sources for the Caenorhabditis nematodes. This prey-predator interaction becomes a model to investigate the effects of each bacterial strain on the nematodes at multiple levels (phenotypes to molecular regulations). To see how the interaction could be, we isolated many Caenorhabditis nematodes and the associated bacteria from the forests. Theoretically, they have been living and evolving, suggesting that they would have specific interaction. In this research, we report the identification of a new environmental bacteria associated with the nematode genus Caenorhabditis in Cat Tien National Park with the 16S rDNA. We identified the bacteria as Microbacterium sp. CFBb57.1. In the second part of our investigation, we investigated the impacts of the bacteria on the longevity and reproduction of the model nematode Caenorhabditis elegans using the control Escherichia coli OP50. The results showed that C. elegans living on CFBb57.1 had extended longevity and they had a reduction in reproduction, presenting a longevity/fecundity tradeoff. Last, in the bacterial preference test, we found their preference was modulated on CFBb57.1 in comparison with the control OP50, suggesting that the worms did not prefer CFBb57.1 over OP50. However, more CFBb57.1-acclimating worms were chemotactic to CFBb57.1, indicating that worms had genetic mechanism(s) to adapt to CFBb57.1. C. elegans responded differently to the Microbacterium bacteria in this study and previous reports. In this study, it first showed the tradeoff and acclimation. Thus, this report will facilitate the studies of how the Caenorhabditis nematodes could evolve the mechanism(s) of tradeoff that was also presented in other bacterial genera and the mechanism(s) of acclimation that would be epigenetic to neutralize the impacts of bacteria.